2022
DOI: 10.7717/peerj.14033
|View full text |Cite
|
Sign up to set email alerts
|

CAV1 alleviated CaOx stones formation via suppressing autophagy-dependent ferroptosis

Abstract: Background Calcium oxalate (CaOx) is the most common type of kidney stone, but the mechanism of CaOx stones formation remains unclear. The injury of renal cells such as ferroptosis and autophagy has been considered a basis for stones formation. Methods We conducted transmission electron microscope (TEM), reactive oxygen species (ROS), malondialdehyde (MDA), glutathione (GSH), and C11-BODIPY analysis to explore whether CaOx could induce autophagy-dependent ferroptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In recent years, with the progressive understanding of ferroptosis, several studies have demonstrated a correlation between ferroptosis and kidney stones. Yang et al [ 55 ] established a rat kidney stone model by injecting glyoxalate and found that the mitochondria in rat RTECs became smaller and increased in membrane density, and the mitochondria were severely damaged. The change of mitochondrial ultrastructure was the morphological characteristic of ferroptosis in the cells, which proved that ferroptosis was involved in the formation of kidney stones.…”
Section: Ferroptosis and Kidney Stonementioning
confidence: 99%
“…In recent years, with the progressive understanding of ferroptosis, several studies have demonstrated a correlation between ferroptosis and kidney stones. Yang et al [ 55 ] established a rat kidney stone model by injecting glyoxalate and found that the mitochondria in rat RTECs became smaller and increased in membrane density, and the mitochondria were severely damaged. The change of mitochondrial ultrastructure was the morphological characteristic of ferroptosis in the cells, which proved that ferroptosis was involved in the formation of kidney stones.…”
Section: Ferroptosis and Kidney Stonementioning
confidence: 99%
“…Additionally, knockdown of NCOA4 alleviated the effects of oxalate on ferroptosis in HK-2 cells [111]. Another study demonstrated that CAV1 reduced CaOx stone formation by blocking autophagy-dependent ferroptosis [112]. CaOx was discovered to trigger autophagy-dependent ferroptosis in both in vivo and in vitro settings, which may contribute to the development of urolithiasis [112].…”
Section: Ferroptosis and Kidney Diseasesmentioning
confidence: 99%
“…Another study demonstrated that CAV1 reduced CaOx stone formation by blocking autophagy-dependent ferroptosis [112]. CaOx was discovered to trigger autophagy-dependent ferroptosis in both in vivo and in vitro settings, which may contribute to the development of urolithiasis [112]. GSEA revealed that the WNT pathway was negatively associated with the stone group, and lipoprotein receptor-related protein 6 (LRP6) was the core gene of the WNT pathway [112].…”
Section: Ferroptosis and Kidney Diseasesmentioning
confidence: 99%
See 2 more Smart Citations